2019
DOI: 10.1101/724823
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diversification of DNA-binding specificity via permissive and specificity-switching mutations in the ParB/Noc protein family

Abstract: Specific interactions between proteins and DNA are essential to many biological processes. Yet it remains unclear how the diversification in DNA-binding specificity was brought about, and what were the mutational paths that led to changes in specificity. Using a pair of evolutionarily related DNAbinding proteins each with a different DNA preference (ParB and Noc: both having roles in bacterial chromosome maintenance), we show that specificity is encoded by a set of four residues at the protein-DNA interface. C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Interestingly, our analysis of available ChIP-seq data (including the 17 chromosomal ParBs from various species produced in E. coli [142] and tested for DNA binding in this heterologous host, as well as two ParBs from V. cholerae and Corynebacterium glutamicum tested in their native hosts) showed that binding to parS half-sites GTTCCAC and GTTTCAC is not a unique feature of P. aeruginosa ParB (Figure 3a,b). ParB of P. aeruginosa and five other ParBs clearly bind to these heptanucleotides even in a heterologous host.…”
Section: Parb Binding To Half-pars: a Novel Aspect Of Parb-dna Interamentioning
confidence: 96%
“…Interestingly, our analysis of available ChIP-seq data (including the 17 chromosomal ParBs from various species produced in E. coli [142] and tested for DNA binding in this heterologous host, as well as two ParBs from V. cholerae and Corynebacterium glutamicum tested in their native hosts) showed that binding to parS half-sites GTTCCAC and GTTTCAC is not a unique feature of P. aeruginosa ParB (Figure 3a,b). ParB of P. aeruginosa and five other ParBs clearly bind to these heptanucleotides even in a heterologous host.…”
Section: Parb Binding To Half-pars: a Novel Aspect Of Parb-dna Interamentioning
confidence: 96%
“…N-terminally His-tagged MBP-tagged ParB (orthologous proteins from various bacterial species) were expressed from E. coli Rosetta (DE3) harboring pET-His-MBP-TEV-DEST::ParB plasmids (Table S1). His6-MBP-ParB proteins were purified via a one-step Ni-affinity column as described previously 56 .…”
Section: Protein Overexpression and Purificationmentioning
confidence: 99%
“…Here, the ability to assess many mutations in parallel and measure even subtle differences in affinity suggests that effects of mutations in trans could be compensated for by concomitant changes in nucleotides flanking cis-regulatory elements to preserve transcriptional responses (Beltran, et al, 2004;Rogers and Bulyk, 2018). In addition, the observation that mutations may stabilize helical conformations to promote DNA binding suggests that these residues could allow formation of permissive binding intermediates (Bloom, et al, 2010;Gong, et al, 2013;Jalal, et al, 2019;McKeown, et al, 2014;Starr, et al, 2017). The higher affinity binding of these permissive binding intermediates could allow TFs to acquire and accommodate additional TF or DNA mutations that would otherwise reduce binding to non-physiological levels, making otherwise inaccessible evolutionary trajectories feasible.…”
Section: Discussionmentioning
confidence: 99%